2023
DOI: 10.3389/fimmu.2023.1247288
|View full text |Cite
|
Sign up to set email alerts
|

Significance of NotchScore and JAG1 in predicting prognosis and immune response of low-grade glioma

Bo Shi,
Fei Ge,
Liangliang Cai
et al.

Abstract: IntroductionLow-grade glioma (LGG) is a prevalent malignant tumor in the intracranial region. Despite the advancements in treatment methods for this malignancy over the past decade, significant challenges still persist in the form of drug resistance and tumor recurrence. The Notch signaling pathway plays essential roles in many physiological processes as well as in cancer development. However, the significance of the pathway and family genes in LGG are poorly understood. MethodsWe conducted gene expression pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…JAG1 was significantly downregulated in the RT plus CSF-1R inhibition group compared with the recurrent RT-treated mice. High levels of JAG1 and NOTCH1/DLL1 were significantly positively associated with short survival in the TCGA cohort, which was consistent with findings in literature [ 18 , 19 ]. Importantly, it has been shown that [ 18 ], Notch1 signaling activity was elevated in GBM tissues, and downregulation of the Notch1 pathway by shRNA and MK0752 significantly inhibited the PI3K/AKT/mTOR signaling pathway and weakened the self-renewal, invasion, and tumor growth ability of glioma initiating cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…JAG1 was significantly downregulated in the RT plus CSF-1R inhibition group compared with the recurrent RT-treated mice. High levels of JAG1 and NOTCH1/DLL1 were significantly positively associated with short survival in the TCGA cohort, which was consistent with findings in literature [ 18 , 19 ]. Importantly, it has been shown that [ 18 ], Notch1 signaling activity was elevated in GBM tissues, and downregulation of the Notch1 pathway by shRNA and MK0752 significantly inhibited the PI3K/AKT/mTOR signaling pathway and weakened the self-renewal, invasion, and tumor growth ability of glioma initiating cells.…”
Section: Discussionsupporting
confidence: 92%
“…This is one of the potential mechanisms underlying the combination therapy (RT plus CSF-1R inhibition) that seemingly mitigated resistance to RT-only [ 12 ] and CSF-1R inhibition-only therapy [ 3 ]. Additionally, experimental results demonstrate that silencing JAG1 yielded a significant decrease in tumor cell proliferation in LGG cell lines, and JAG1 potentially influences PD-L1 in LGG by regulating the PI3K/AKT signaling pathway [ 19 ]. The critical role of the Hippo pathway has been investigated in GBM, and the results suggested that the activation of YAP1/WWTR1 was associated with poor prognosis in GBM [ 20 ].…”
Section: Discussionmentioning
confidence: 99%